2018
DOI: 10.1186/s12890-018-0671-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health applications in self-management of patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis of their efficacy

Abstract: BackgroundMobile health applications are increasingly used in patients with Chronic Obstructive Pulmonary Disease (COPD) to improve their self-management, nonetheless, without firm evidence of their efficacy. This meta-analysis was aimed to assess the efficacy of mobile health applications in supporting self-management as an intervention to reduce hospital admission rates and average days of hospitalization, etc.MethodsPubMed, Web of Science (SCI), Cochrane Library, and Embase were searched for relevant articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
2
56
1
3
Order By: Relevance
“…The results from our pooled data meta-analysis do not identify a statistically significant effect on measures of physical function or QoL. Previous meta-analyses have identified no differences in physical function (using the 6-minute walk test) 10 , dyspnea 10 , and average days of hospitalization 9 , but have noted that the intervention arm was favored for physical activity 10 and a lower risk of hospital admissions 9 .…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…The results from our pooled data meta-analysis do not identify a statistically significant effect on measures of physical function or QoL. Previous meta-analyses have identified no differences in physical function (using the 6-minute walk test) 10 , dyspnea 10 , and average days of hospitalization 9 , but have noted that the intervention arm was favored for physical activity 10 and a lower risk of hospital admissions 9 .…”
Section: Discussioncontrasting
confidence: 75%
“…Several systematic reviews have been conducted exploring applications to support self-management of COPD, but questions remain regarding their potential to improve clinical and nonclinical outcomes. Meta-analyses to date have pooled trials investigating hospital admissions 9 , physical activity 10 , physical function 10 , dyspnea 10 , and exacerbations 11 . However, reviews to date have used varying eligibility criteria for inclusion, excluding tablet computers 11 , excluding trials with any healthcare professional input 12 , excluding trials shorter than 1 month in duration 9 , or only including trials reporting hospitalization or exacerbation events 9,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e list of excluded literature studies and reasons of exclusion are displayed in Appendix 2 in Supplementary materials. us, a total of 8 SRs and MAs [16][17][18][19][20][21][22][23] were finally included in this overview. e study selection process is shown in Figure 1.…”
Section: Study Identificationmentioning
confidence: 99%
“…We included six systematic review and meta-analysis [16-18, 20, 22, 23], one meta-analysis [19], and one systematic review, which were published between 2011 and 2019, with four from Asian countries [16][17][18][19] and four from European countries [20][21][22][23], and all databases reviews retrieved ranged from one to six, with PubMed, Embase, and Cochrane Library as the most widely searched databases. e number of RCTs included in each review ranged from 3 to 28, and the total participants ranged from 391 to 3645.…”
Section: Characteristics Of Included Reviewmentioning
confidence: 99%